COMPARATIVE STUDIES OF THE PHYSIOLOGICAL – CHEMICAL PROPERTIES OF SOME TOMATOES CULTIVARS UNDER ARID ZONE CONDITIONS - Mohamed Mostafa Mahmoud Abdelkader; M. Yu. Puchkov; L. P. Ionova; M. A. Lysakov (Овощи России, 2018)
Currently, in southern regions of Russia, mainly, tomatoes of foreign breeding are grown. First of all, this is due to the fact that until recently Russian varieties could not compete with foreign in terms of storage, transportation and guaranteed yield. But in connection with sharp changes in weather conditions, in the direction of increasing critical temperatures, the relevance of cultivating modern varieties of tomato of Russian selection possessing high heatresistant characteristics becomes relevant. The varieties of Tomato Selection of All-Russian Scientific Research Institute of Irrigation Vegetable and Melon Growing served as an object of research. The biochemical properties of fruits depend very strongly on the conditions of growth of the crop and on the genetic potential of the variety. The most important biochemical indicators of tomato fruit are the amount of dry matter, the amount of sugars, the pH of fruit juice, carotene, vitamin C (ascorbic acid) and the amount of nitrates. These indicators determine the quality of tomato fruits (products). Five varieties of tomatoes were evaluated for quality changes. The content of solids is maximally in the Morayan variety 6.60±0.04%, the lowest in the Cascader variety is 4.06±0.07%, therefore the most optimal technical properties for the Morayan variety. The content of sugars is maximally in the Moryan variety 4.36±0.05%, the lowest in the stunt Kaskader 2.22±0.04%. The maximum pH of the fruit juice in the variety Cascader is 3.75±0.07 less acidic juice medium, the most acidic medium in the Malinovka variety is 2.75±0.03. The maximum content of carotene in the Moryan variety is 3.03±0.07 mg%, the minimum in the Kaskader variety is 1.26±0.05 mg%. The largest amount of nitrates is able to accumulate a variety of Petrovsky 68.3±0.04 mg%, the minimum quantity in the Supergol variety is 19.0±0.04mg%. The content of ascorbic acid is the highest in the Moryan variety 21.0±0.03 mg%, the lowest in the Petrovsky variety 9.77±0.02.